NALISIS PERILAKU DISIPLIN ANAK USIA 5-6 TAHUN - Faujiah, Sonia; Mulyadi, Sima; Sumardi, Sumar (Universitas Pendidikan Indonesia (UPI), 2020)
The family has a very significant role in implementing the discipline behavior of children at home. Theapplication of children's disciplinary behavior at home should be done in the child's daily activities.This research was conducted in Mangkubumi Village, Mangkubumi District, Tasikmalaya City which aimsto describe the discipline behavior of children aged 5-6 years at home. The subjects in this study were 31parents who had children aged 5-6 years and had taught children to be disciplined at home. This researchuses a quantitative approach with descriptive research methods. Data collection techniques used werequestionnaires and documentation. The results of research findings and data analysis show that disciplinarybehavior of children aged 5-6 years includes sleep discipline behavior, prayer discipline behavior, Al-Quranreading discipline behavior, bathing discipline behavior, eating discipline behavior, learning disciplinebehavior. the result is that there are no children who have excellent discipline behavior (0%),13 children have good disciplinary behavior (41.94%), 8 children have moderate disciplinary behavior(25.81%), 9 children have poor disciplinary behavior (29.03%), and 1 child has very poor disciplinarybehavior (3,23%). The average result of disciplinary behavior of children aged 5-6 years is 75.00, meaningthat the average age of children 5-6 years in Mangkubumi Village, Mangkubumi District, Tasikmalaya Cityhas good discipline behavior.Keluarga memiliki peran yang sangat signifikan dalam menerapkan perilaku disiplin anak di rumah.Penerapan perilaku disiplin anak di rumah seyogiyanya dilakukan dalam kegiatan sehari-hari anak.Penelitian ini dilakukan di Kelurahan Mangkubumi, Kecamatan Mangkubumi Kota Tasikmalaya yangbertujuan untuk mendeskripsikan perilaku disiplin anak usia 5-6 tahun di rumah. Subjek dalam penelitian iniadalah 31 orang tua yang memiliki anak usia 5-6 tahun dan telah mengajarkan anak untuk disiplin di rumah.Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian deskriptif. Teknikpengumpulan data yang digunakan adalah angket dan dokumentasi. Hasil dari temuan penelitian dan analisisdata menunjukan bahwa perilaku disiplin anak usia 5-6 tahun meliputi perilaku disiplin tidur, perilakudisiplin sholat, perilaku disiplin membaca Al-Quran, perilaku disiplin mandi, perilaku disiplin makan,perilaku disiplin belajar. Hasilnya adalah belum terdapat anak yang memiliki perilaku disiplin yang sangatbaik (0%), 13 anak memiliki perilaku disiplin baik (41,94%), 8 anak memiliki perilaku disiplin sedang(25,81%), 9 anak memiliki perilaku disiplin kurang (29,03%), dan 1 anak memiliki perilaku disiplin sangatkurang (3,23%). Hasil rata-rata perilaku disiplin anak usia 5-6 tahun adalah 75,00, artinya rata-rata anak usia5-6 tahun di Kelurahan Mangkubumi, Kecamatan Mangkubumi Kota Tasikmalaya memiliki perilaku disiplinbaik.